Pengabdian Kepada Masyarakat Program Kemitraan Masyarakat Mandiri (PKM Mandiri) Pengolahan Sampah Dan Proses Pembuatan Pupuk Kompos Di UPTD SDN 35 Gedong Tataan Kabupaten Pesawaran Tahun 2026 - Linda Barus; Suami; Farizal (STIKES Columbia Asia Medan, 2026)
This community service activity focused on waste management and composting in elementary schools. Daily activities in schools generate organic and inorganic waste, which, if not managed properly, can cause environmental pollution and increase the risk of health problems. Students' lack of knowledge and habits in sorting and processing waste is one of the contributing factors to this problem. Therefore, early environmental education is needed to foster caring and responsible behavior in waste management. Improving students' knowledge and skills in sorting waste and processing organic waste into compost is an effort to create a clean and environmentally friendly school environment. The activity was carried out over one day through counseling, interactive discussions, demonstrations, and hands-on practice of waste sorting and making simple compost using presentation media and real-world examples. Students demonstrated active and enthusiastic participation throughout the activity. There was an increase in understanding of the types of waste, the importance of proper waste management, and the stages of composting. Students were able to practice sorting organic and inorganic waste and understand the basic process of composting. This activity was effective in increasing students' knowledge, awareness, and skills related to waste management and composting. The combination of interactive outreach methods and hands-on practice contributes to fostering environmentally conscious behavior and supporting the creation of a clean, healthy, and sustainable school environment.